An interactive activation and competition model of person knowledge, suggested by proactive interference by traits spontaneously inferred from behaviours. (20th June 2015) - Wang, Yuanbo E.; Higgins, Nancy C.; Uleman, James S.; Michaux, Aaron; Vipond, Douglas
Abstract : People unconsciously and unintentionally make inferences about others' personality traits based on their behaviours. In this study, a classic memory phenomenon – proactive interference (PI) – is for the first time used to detect spontaneous trait inferences. PI should occur when lists of behaviour descriptions, all implying the same trait, are to be remembered. Switching to a new trait should produce 'release' from proactive interference (or RPI). Results from two experiments supported these predictions. PI and RPI effects are consistent with an interactive activation and competition model of person perception (e.g., McNeill & Burton, 2002, J. Exp. Psychol ., 55A, 1141), which predicts categorical organization of social behaviours based on personality traits. Advantages of this model are discussed.